Prognostic value of post-operative C-reactive protein-based inflammatory biomarkers in colorectal cancer patients: systematic review and meta-analysis - Gwenzi, Tafirenyika; Zhu, Anna; Schrotz-King, Petra; Schöttker, Ben; Hoffmeister, Michael; Edelmann, Dominic; Brenner, Hermann (Clinical epidemiology, 2023)
Post-operative inflammation in cancer patients can be modulated by drugs and diets, but evidence on its prognostic role, which would be crucial for personalized treatment and surveillance schemes, remains rather limited. We aimed to systematically review and meta-analyse studies on the prognostic value of post-operative C-reactive protein (CRP)-based inflammatory biomarkers among patients with colorectal cancer (CRC) (PROSPERO#: CRD42022293832). PubMed, Web of Science and Cochrane databases were searched until February 2023. Studies reporting associations between post-operative CRP, Glasgow Prognostic Score (GPS) or modified Glasgow Prognostic Score (mGPS) with overall survival (OS), CRC-specific survival (CSS) and recurrence-free survival (RFS) were included. Hazard ratios (HRs) with 95% confidence intervals (CIs) for the predictor-outcome associations were pooled using R-software, version 4.2. Sixteen studies (n = 6079) were included in the meta-analyses. Elevated post-operative CRP was a predictor of poor OS, CSS and RFS compared with low CRP levels [HR (95% CI): 1.72 (1.32– 2.25); 1.63 (1.30– 2.05); 2.23 (1.44– 3.47), respectively]. A unit increase in post-operative GPS predicted poor OS [HR (95% Cl): 1.31 (1.14– 1.51)]. Moreover, a unit increase in post-operative mGPS was associated with poor OS and CSS [HR (95% Cl): 1.93 (1.37– 2.72); 3.16 (1.48– 6.76), respectively]. Post-operative CRP-based inflammatory biomarkers have a significant prognostic role for patients with CRC. Prognostic value of these easy-to-obtain routine measurements thereby seems to outperform most of the much more complex blood- or tissue-based predictors in the current focus of multi-omics-based research. Future studies should validate our findings, establish optimal time for biomarker assessment and determine clinically useful cut-off values of these biomarkers for post-operative risk-stratification and treatment-response monitoring.
Veröffentlicht: 27. Juni 2023
Gesehen am 01.08.2023